Blood and fire : toward a global anthropology of labor - Kasmir, Sharryn; Carbonella, August (Dislocations., 2014)
Based on long-term fieldwork, six vivid ethnographies from Colombia, India, Poland, Spain and the southern and northern U.S. address the dwindling importance of labor throughout the world. The contributors to this volume highlight the growing disconnect between labor struggles and the advancement of the greater common good, a phenomenon that has grown since the 1980s. The collection illustrates the defeat and unmaking of particular working classes, and it develops a comparative perspective on the uneven consequences of and reactions to this worldwide project. In Blood and Fire char.